2014
DOI: 10.1007/s00122-014-2393-9
|View full text |Cite
|
Sign up to set email alerts
|

A down-regulated epi-allele of the genomes uncoupled 4 gene generates a xantha marker trait in rice

Abstract: A γ-ray-induced xantha trait is epigenetically controlled by the genomes uncoupled 4 gene with enhanced promoter segment methylation and down-regulated expression in rice. For easy testing and to increase varietal purity, a xantha mutation (xnt), which turns plants yellow and makes them visually distinguishable from normal green rice, has been generated and bred into male sterile lines for hybrid rice production. The xnt locus was previously fine mapped to a ~100-kb interval on chromosome 11, but its identity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…There were no reports describing GUN4 from other plant species until we revealed that an epi-allele of OsGUN4 is responsible for the xantha marker trait (Li et al, 2014). This previous study remains the only one involving a GUN4 from a crop plant.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…There were no reports describing GUN4 from other plant species until we revealed that an epi-allele of OsGUN4 is responsible for the xantha marker trait (Li et al, 2014). This previous study remains the only one involving a GUN4 from a crop plant.…”
Section: Discussionmentioning
confidence: 83%
“…Mutations to any of these genes may reduce or even eliminate chlorophyll biosynthesis, leading to leaf color changes (Liu et al, 2007, 2016; Yoo et al, 2009; Tian et al, 2013; Wang et al, 2014; Zhang et al, 2015; Yang et al, 2016). Through gene mapping and additional studies, the mutant gene responsible for the xantha marker trait of HYB was identified as a mutated OsGUN4 ( genomes uncoupled 4 ) (Chi et al, 2010; Li et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…The results were consistent with a sharp reduction of SRL1 expression downstream of the third exon‐encoded region, indicating that DNA methylation in cld1 plays essential roles in the regulation of SRL1 expression. To further validate the correlation between the cld1 phenotype and SRL1 methylation, we treated cld1 seeds with 5‐aza‐2′‐deoxycytidine (5‐aza‐dC), an inhibitor of DNA methylation (Miura et al ., ; Li et al ., ). All the cld1 seedlings from untreated seeds showed the leaf‐rolling phenotype, whereas 63.1% of cld1 seedlings from 5‐aza‐dC‐treated seeds exhibited a flat leaf phenotype (Figure g).…”
Section: Resultsmentioning
confidence: 97%
“…Epialleles have been reported in several plant species, including maize (Brink, 1956;Banks et al, 1988;Das and Messing, 1994;Hollick and Chandler, 2001) and rice (Miura et al, 2009(Miura et al, , 2010Wang et al, 2010;Zhang et al, 2012;Li et al, 2014). The phenotypes of these epialleles are affected by DNA methylation status and/or histone modification resulting in the alteration of gene expression.…”
Section: Dna Methylation Of Kala4mentioning
confidence: 99%